Pengaruh Brand Image (RANNA) dan Promosi e-WOM terhadap Daya Beli Konsumen Mahar Akrilik di Galeri Mahar Cantik Jember - Munawir, Salsabila (Jurnal Ekonomi Akuntansi dan Manajemen, 2025)
This study aims to analyze the influence of Brand Image and Electronic Word of Mouth (e-WOM) promotion on consumer purchasing power of acrylic wedding at Galeri Mahar Cantik Jember. A quantitative approach using a survey method was employed, involving 93 respondents who were active consumers of the Instagram account @maharcantikjember. Data were collected via questionnaires and analyzed using validity and reliability tests, multiple linear regression, t-test, and F-test with SPSS 30. The results indicate that both brand image and ewom significantly affect consumer purchasing power, both partially and simultaneously. Brand image showed the most dominant effect with a coefficient value of 0.337. The implication of this research emphasizes the importance of strengthening brand image and digital promotion in enhancing consumer purchasing behavior, particularly in the creative wedding industry. These findings contribute to digital marketing strategies and business development through social media platforms Keywords: Brand Image, EWOM, Purchasing Power, Digital Marketing, Acrylic Wedding